CCNP Enterprise Wireless Design ENWLSD 300-425 and Implementation ENWLSI 300-430 Official Cert Guide Designing & Implementing Cisco Enterprise Wireless Networks - Henry, Jerome; Barton, Robert; Hucaby, Dave (Cisco Press, 2020)
CCNP Enterprise Wireless Design ENWLSD 300-425 and Implementation ENWLSI 300-430 Official Cert Guide from Cisco Press allows you to succeed on the exam the first time and is the only self-study resource approved by Cisco. Wireless networking experts Jerome Henry, Robert Barton, and David Hucaby share preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills. This complete study package includes A test-preparation routine proven to help you pass the exams Do I Know This Already? quizzes, which allow you to decide how much time you need to spend on each section Chapter-ending Key Topic tables, which help you drill on key concepts you must know thoroughly The powerful Pearson Test Prep Practice Test software, complete with hundreds of well-reviewed, exam-realistic questions, customization options, and detailed performance reports An online, interactive Flash Cards application to help you drill on Key Terms by chapter A final preparation chapter, which guides you through tools and resources to help you craft your review and test-taking strategies Study plan suggestions and templates to help you organize and optimize your study time This official study guide helps you master all the topics on the CCNP Designing Cisco Enterprise Wireless Networks (ENWLSD 300-425) exam and CCNP Implementing Cisco Enterprise Wireless Networks (ENWLSI 300-430) exam, including Wireless Site Survey Wired and Wireless Infrastructure Mobility WLAN High Availability FlexConnect QoS on a Wireless Network Multicast Location Services and Advanced Location Services Security for Wireless Client Connectivity Monitoring Device Hardening.
Online resource; Title from title page (viewed September 18, 2020)
Keywords: Business enterprises -- Computer networks; Data transmission systems -- Study guides -- Examinations; Electronic data processing personnel -- Certification; Wireless communication systems -- Study guides -- Examinations; Wireless LANs -- Study guides -- Design and construction -- Examinations; Entreprises; Réseaux d'ordinateurs; Transmission sans fil; Examens; Guides de l'étudiant; Business enterprises; Computer networks; Electronic data processing personnel; Certification; examination study guides; Study guides; Guides de l'étudiant